PEMETAAN PRASARANA DAN KONTUR KAMPUS UNIVERSITAS WIRARAJA BERDASARKAN CITRA PENGINDRAAN JAUH - Deshariyanto, Dwi; Fansuri, Subaidillah; Diana, Anita Intan Nura (Jurnal Ilmiah MITSU (Media Informasi Teknik Sipil Universitas Wiraraja), 2023)
Wiraraja University campus from its establishment in 1986 to 2023 has a period of 37 years which has experienced many developments, especially learning infrastructure. The development of infrastructure needs to be mapped to determine the distribution of learning infrastructure on the Wiraraja University campus. The utilization of geographic information system (GIS) technology and the development of infrastructure on the Wiraraja University campus, it is necessary to map the infrastructure and contours on the Wiraraja University campus which will later obtain an overview of the infrastructure. The purpose of the study was to determine the infrastructure map and the percentage of infrastructure to the overall land and contour map of Wiraraja University campus. The research used Google Earth and ArcMap. The research data collection was carried out by field survey and data collection of infrastructure on the campus of Wiraraja University and the research data was carried out by frequency analysis. Land use on the campus of Wiraraja University is divided into the categories of buildings, sports fields, covered and open parking, parks, roads and vacant land. The land area of Wiraraja University campus based on Google Earth images with the digitization method is 22,711.86 m2. The largest land use is used as a building at 37.54%, while the smallest land use is used as a covered parking lot at 1.78%. The elevation of the Wiraraja University campus is between 3.67 - 5.94 m elevation and the highest elevation is 5.94 meters and the lowest elevation is 3.67 meters above mean sea level.